2018
DOI: 10.1002/macp.201700607
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Supramolecular Polylactides Gels Obtained via Stereocomplexation

Abstract: In this paper, stereocomplexation is used as a driving force for the formation of 3D polymer networks by hydrogen bonding cross‐linking between complementary enantiomeric polylactides (PLAs). Thus, the formation of the gels after the mixing of equimolar solutions of l‐ and d‐star‐shaped PLAs in the biocompatible N‐methyl‐2‐pyrrolidone (NMP) is observed. The utility of star‐shaped polymers facilitates the cross‐linking of macromolecules by increasing the number of functional end groups. Moreover, the well‐estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Furthermore, the CH 3 and CH bending region, between 1,250 and 1,400 cm −1 , showed asymmetric and broad bands for Pyr-L compared to Pyr-L/Pyr-D SC, being the δ(CH) band high-frequency shift for the stereocomplex (~10 cm −1 ), as previously observed by Kister et al (1998). The band at 920 cm −1 , observed in Pyr-L and assigned to the α-helix of an enantiomeric PLA, disappeared in and Pyr-L/Pyr-D SC and a new band appeared at 909 cm −1 , corresponding to β-helix, characteristic of the stereocomplex, accordingly to previous report by Michalski et al (2018). Finally, after stereocomplexation the ν(C-COO) stretching mode at 872 cm −1 is shifted at higher frequency and appears less asymmetric compared to the corresponding band in Pyr-L spectrum, thus further confirming the successful formation of the stereocomplex crystallites.…”
Section: Resultssupporting
confidence: 88%
“…Furthermore, the CH 3 and CH bending region, between 1,250 and 1,400 cm −1 , showed asymmetric and broad bands for Pyr-L compared to Pyr-L/Pyr-D SC, being the δ(CH) band high-frequency shift for the stereocomplex (~10 cm −1 ), as previously observed by Kister et al (1998). The band at 920 cm −1 , observed in Pyr-L and assigned to the α-helix of an enantiomeric PLA, disappeared in and Pyr-L/Pyr-D SC and a new band appeared at 909 cm −1 , corresponding to β-helix, characteristic of the stereocomplex, accordingly to previous report by Michalski et al (2018). Finally, after stereocomplexation the ν(C-COO) stretching mode at 872 cm −1 is shifted at higher frequency and appears less asymmetric compared to the corresponding band in Pyr-L spectrum, thus further confirming the successful formation of the stereocomplex crystallites.…”
Section: Resultssupporting
confidence: 88%
“…As a characteristic feature of stereoselective intermolecular interaction, the chain length and stoichiometry of enantiomeric chains in a specific SC are usually fixed. , In this sense, molecular weight and composition (i.e., ratio between two species) are the two direct and critical factors dictating the formation of SCs. , Nevertheless, unlike biomacromolecules with definite chemical structure and uniform size, synthetic polymers are essentially a mixture of macromolecules with varying chain lengths (known as molecular weight distribution) . Due to the multicomponent nature and miscellaneous constituents, it is exceedingly challenging to precisely control the stoichiometry and match the length of the enantiomeric pairs .…”
Section: Introductionmentioning
confidence: 99%
“…[60] SC gels were mainly reported in amphiphilic block copolymers. [93][94][95] Michalski et al reported the formation of SC gel using star-shaped enantiomeric PLAs in organic solvent at room temperature. [95] Different from these studies, Praveena et al investigated the structural changes of the blend gels in multiple length scales during heating.…”
Section: Solvent-induced Gel Formation In Pllamentioning
confidence: 99%
“…[93][94][95] Michalski et al reported the formation of SC gel using star-shaped enantiomeric PLAs in organic solvent at room temperature. [95] Different from these studies, Praveena et al investigated the structural changes of the blend gels in multiple length scales during heating. [60] For comparison, experiments were conducted with both homopolymer gels and blend gels.…”
Section: Solvent-induced Gel Formation In Pllamentioning
confidence: 99%